The Factors Influencing Early Marriage among Women - Triyoolanda, Anggun; Indriani, Fatma; Nurhayati (Newinera Publisher, 2023)
A marriage that is carried out prematurely or at a too young age is something that is contrary to the law on marriage. Objective: This research is to determine the relationship between factors that influence young marriage in young couples. Method: The study used a descriptive analytical design with a cross-sectional approach. A total of 97 couples in AFD 2 Bahbutong, Sidamanik District, Simalungun Regency, were selected as respondents through a simple random sampling technique. The dependent variable was early marriage, while the independent variables included self-will, family/parental support, education, and economic factors. Data were collected through questionnaires and analyzed using Pearson correlation. Results: The study showed that self-will had a strong positive relationship with early marriage (r=0.605, p<0.001). Family support had a moderate positive relationship (r=0.417, p<0.001), while education factors had a strong negative relationship (r=-0.650, p<0.001). Economic factors also had a moderate negative relationship with early marriage (r=-0.453, p<0.001). Conclusion: All independent variables showed a significant relationship with early marriage. Therefore, interventions to reduce early marriage need to be focused on increasing access to education, economic empowerment, and family awareness of the negative impacts of early marriage.Key words: Young marriage, own will, economic factors, family factors.